Acute and Chronic Neural Stimulation via Mechano-Sensitive Ion Channels - Tay, Andy Kah Ping (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This book describes the tools, developed by the author, for perturbing endogenous mechano-sensitive ion channels for magneto-mechanical neuro-modulation. He explores the ways in which these tools compare against existing ones such as electricity, chemicals, optogenetics, and techniques like thermos/magneto-genetics. The author also reports on two platforms-magnetic ratcheting and magnetic microfluidics for directed evolution and high throughput culture of magnetotactic bacteria-that produce high quality magnetic nanoparticles for biomedical applications like neural stimulations. This thesis was submitted to and approved by the University of California, Los Angeles. Introduces technology for non-invasive control of neural activities that offer deep tissue penetration and controllable dosage; Examines the effects of biomechanical forces on cellular functions; Explores how to improve the reproducibility and uptake of magnetic tools for non-invasive neural modulation.